2010
DOI: 10.1039/c0jm00376j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of highly visible-light active N-doped TiO2 photocatalyst

Abstract: A series of N-doped anatase TiO 2 samples have been prepared using a solvothermal method in an organic amine/ethanol-water reaction system. The effects of different starting N : Ti atomic ratios on the catalysts structure, surface property and catalytic activity have been investigated. The photocatalytic activity and stability of the N-doped TiO 2 samples were evaluated through using the decomposition of Methylene blue (MB) and Methyl orange (MO) as model reaction under visible light irradiation. Characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
397
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(422 citation statements)
references
References 56 publications
20
397
1
4
Order By: Relevance
“…It is remarkable that the E 1g vibration band, it is very intense and acute, similar conditions have been reported by other researchers [31], [28], [25]. In Table 1 shows that after the doping process with nitrogen, the N-TiO 2 film has a vibrational band right shifted, indicating that the particle size has been increased, this effect has been observed by others authors [32], [33]. Later is consistent with the results of XRD.…”
Section: Resultssupporting
confidence: 81%
“…It is remarkable that the E 1g vibration band, it is very intense and acute, similar conditions have been reported by other researchers [31], [28], [25]. In Table 1 shows that after the doping process with nitrogen, the N-TiO 2 film has a vibrational band right shifted, indicating that the particle size has been increased, this effect has been observed by others authors [32], [33]. Later is consistent with the results of XRD.…”
Section: Resultssupporting
confidence: 81%
“…To be noted that the range of 397.5 to 400.3 eV was corresponding to Ti-N-O. After the peak splitting of N 1s (Figure 4), the peaks also appeared in the regions of ď397.5 eV (N-Ti-N) and ě404 eV ascribing to NO x [33,34]. This further confirmed that N of the Mn/Ti-N-WACF samples substituted some of the O atoms in the TiO 2 lattice.…”
Section: Xps Analysismentioning
confidence: 99%
“…For the N 1s, the high binding energy of around 406 eV can be assigned to nitrogen species bound to various surface oxygen sites (NO or NO 2 molecules) [20]. The N 1s peak at 399-400 eV can be attributed to the nitrogen in the form of Ti-N-O linkage [21].…”
Section: Chemical Analysis Of the Ntk Catalystsmentioning
confidence: 99%